Pengaruh Sistem Informasi Akuntansi Retribusi Boarding Pass Pelabuhan Terhadap Sistem Pengendalian Internal - Karmila Karmila; Decky Hendarsyah (JAS (Jurnal Akuntansi Syariah), 2019)
Accounting information systems are needed in supporting the effectiveness of internal control. The purpose of this study was to determine how the influence of existing accounting information systems in the company on the implementation of internal control. Researchers used descriptive and quantitative methods by distributing questionnaires. From the research results, it turns out that PT. Pelabuhan Indonesia I (Persero) Dumai Branch has implemented an Accounting Information System of port boarding pass fees and an adequate Internal Control System. The Accounting Information System of port boarding pass fees applied to affect the Internal Control System but the effect is not strong. Then the application of the Accounting Information System of port boarding pass fees and the Internal Control System is in accordance with the Islamic perspective.